2014
DOI: 10.1086/678927
|View full text |Cite
|
Sign up to set email alerts
|

The Bumpy Road of Demand Growth—An Application to Atlantic Salmon

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 41 publications
(34 reference statements)
2
21
0
Order By: Relevance
“…Societal feedback cycles generally address challenges associated with food security or environmental concerns, through enabling the substitution of international supply (3), or through production regulation (11), ( Figure 3 shows that as demand (8) increases social license concerns (5) rise, this results in a reduction in political support (12) and a hardening of the regulatory authority's attitude (11) such that the space (4) for expansion is constrained. This leads to a lower equilibrium level of aquaculture production (1), increased price (6) through the supply and demand (8) mechanism and consequently a resultant reduction in societal concern.…”
Section: Salmon Aquaculture's System Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Societal feedback cycles generally address challenges associated with food security or environmental concerns, through enabling the substitution of international supply (3), or through production regulation (11), ( Figure 3 shows that as demand (8) increases social license concerns (5) rise, this results in a reduction in political support (12) and a hardening of the regulatory authority's attitude (11) such that the space (4) for expansion is constrained. This leads to a lower equilibrium level of aquaculture production (1), increased price (6) through the supply and demand (8) mechanism and consequently a resultant reduction in societal concern.…”
Section: Salmon Aquaculture's System Dynamicsmentioning
confidence: 99%
“…For instance, Sha et al (2015) show a strong impact of negative media coverage on US salmon imports, whilst Liu et al, (2016) found little impact of media coverage on salmon demand in Norway. It is also a relative issue, since as demand for salmon has been increasing rapidly globally as well as in main regions (Braekkan et al, 2014), the impact of social concerns may well result from the pace of the demand growth rather than the sign of this interrelationship.…”
Section: Change Dynamicsmentioning
confidence: 99%
“…Norway is the world's second largest seafood exporter, and farmed salmon accounts for close to two thirds of the value of Norwegian seafood exports (Norway Exports 2017). Norwegian production exceeds domestic consumption, and the vast majority (~95%) of salmon from Norway is exported (Asche and Bjørndal, 2011;Braekkan and Thyholdt, 2014). From 2006From -2014 different countries imported salmon from Norway, and growth in production has required growth in markets to sustain value.…”
Section: Introductionmentioning
confidence: 99%
“…Marsh 2003use a method for measuring total shifts in demand that vary independently between years in the form of an index approach, and apply the index to measure demand shifts in the US retail beef market. The approach was popularized by Purcell (1998), and has in recent years been applied to create demand indices for salmon and lamb (Asche, Dahl, Gordon, Trollvik, & Aandahl, 2011;Braekkan & Thyholdt, 2014;Shiflett, Purcell, & Marsh, 2007) as well as several product forms of beef and pork in the US (Tonsor & Schroeder, 2017). We extend the approach by decomposing the total demand shift into predicted and unexplained impacts on demand, in line with the distinction made by Taylor &Taylor (1993) and Karagiannis & Velentzas (2004).…”
Section: Introductionmentioning
confidence: 99%